Cultivares de trigo indicadas para o Cerrado em diferentes condições hídricas do latossolo vermelho distrófico - Guedes, Paulo Otávio Aldaves dos Santos (2021)
The Brazilian Cerrado presents stability in its climate, mainly in relation to rainfall, being characterized in two well defined seasons: a rainy and a dry season. Climate components are in constant interaction with plants and are predictors of plant growth and development processes. Amid these characteristics, the supply of water and its consumption become relevant. The objective of this work was to submit three wheat cultivars, BRS264, BRS394, BRS404, indicated for the central region of Brazil, submitted to five soil water tensions: 12; 24; 36; 48 and 60kPa; in a greenhouse arranged in pots under a randomized block design, 5X3 factorial scheme, with five replications. The monitoring of irrigations was through the reading of the capacitance sensor (model-ML3, Delta T). Phytometric characteristics were evaluated: plant height, shoot dry mass, water use efficiency in shoot dry mass production, root fresh mass, root dry mass, root volume and yield responses such as spikelets per spike, grains per ear, grain mass per ear, average grain mass, yield, water use efficiency in grain production and harvest index; the number of days in the cycle of each treatment was also evaluated. Cultivar BRS394 has the highest averages in plant height, shoot dry mass, water use efficiency in shoot dry mass production, root dry mass, number of spikelets per spike, average grain mass per spike, average grain mass, grain production, water use efficiency for grain production under 24kPa tension and the shortest cycle. Cultivar BRS264 stands out in average mass of grains per ear, efficiency of water use for grain production under 12kPa tension and in harvest index. BRS404 had one of the highest averages in the number of spikelets per spike and the longest cycle. The soil water tension of 12KPa obtained the best results, from 24kpa onwards, there is a decrease in the values of the analyzed variables less in the crop cycle that was affected by moisture, the smallest cycle occurred at the tension of 12kPa.